Analisis Determinan Cadangan Kerugian Penurunan Nilai pada Bank Panin Dubai Syariah Tahun 2015-2022 - Endang Lufita; Rizky Nur Ayuningtyas Putri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing To Deposit Ratio (FDR), Nett Perfoming Financing (NPF), Return Of Equity (ROE), and Size on Loan Loss Provision (LLP). This study used descriptive quantitative methods by analyzing regression time series data processed using the Eviews 10 application. In this study there were six variables consisting of one dependent variable and five independent variables. The dependent variable in this study is Loan Loss Provision (LLP) while the independent variables are Capital Adequacy Ratio (CAR), Financing To Deposit Ratio (FDR), Nett Perfoming Financing (NPF), Return Of Equity (ROE), and Size. This study found that the CAR variable partially had a significant positive effect on LLP. The FDR variable partially has a non-significant negative effect on Bank Panin Dubai Sharia's LLP. NPF has a non-significant positive effect on Bank Panin Dubai Syariah's LLP. ROE variables and Size variables partially have a significant negative effect on Bank Panin Dubai Sharia's LLP. The variables CAR, FDR, NPF, ROE, and Size together (simultaneously) have a significant effect on LLP.